Can You Map Global Financial Stability? - Puig, Jaume (IMF Working Papers; Working Paper ;, 2010)
The Global Financial Stability Map was developed as a tool to interpret the risks and conditions that impact financial stability in a graphical manner. It complements other existing tools for assessing financial stability, and seeks to overcome some of the drawbacks of earlier approaches. This paper provides the motivation for the tool, a detailed discussion of its construction, including the choice of risk factors and conditions, a description of the underlying indicators, and a discussion on how the final assessment is determined. When applied to past events of financial instability, the Global Financial Stability Map performs reasonably well in signaling risks to stability, as well as in characterizing the depth of crisis episodes.